INCEFA-PLUS Programme Overview and Update. (2016) - Mottershead, K.J.; Bruchhausen, M.; Metais, T.; Cicero, S.
Abstract: INCEFA-PLUS is a five year project supported by the European Commission HORIZON2020 programme which commenced in mid 2015. 16 organisations from across Europe have combined forces to deliver new experimental data and a fatigue assessment procedure which will support the development of improved guidelines for assessment of environmental fatigue damage to ensure safe operation of nuclear power plants. Prior to the start of INCEFA-PLUS, an in-kind study was undertaken by several European organisations with the aim of developing the current state of the art for this technical area. This study identified three experimental variables which required further study in order to support improved assessment methodology for environmental fatigue, namely the effects of mean stress/strain, hold time and surface finish. Within INCEFA-PLUS, the effects of these three variables, plus strain amplitude, on fatigue endurance of austenitic stainless steels in light water reactor environments are therefore being studied experimentally. The data obtained will be collected and standardised in an online environmental fatigue database. In order to facilitate the exchange of fatigue data a standardized data format will be developed in the framework of a CEN workshop, to which international participants are welcome to participate. The outcome of the workshop will be a pre-normative document, a CEN Workshop Agreement (CWA) which will set a standard for enabling the exchange of fatigue data not only within the project but within the fatigue community. Based on the data generated and the resulting improvement in understanding, it is planned that INCEFAPLUS will develop and disseminate methods for including the new insights into assessment procedures for environmental fatigue degradation. This will take better account of the effects of mean strain, hold time and surface finish. This paper will provide more details on the background to this project and the way the project is organized to meet its objectives. Details will be provided as to how uncertainties due to variations in testing practice and specimen preparation have been minimized. Additionally, the choices associated with testing for the effects of surface finish, hold time and mean stress will be described along with the status of decisions so far within the project. The paper will also report current status of the project and when findings are likely to be disseminated.